Pterophoridae (Lepidoptera) fauna of the Republic of Tuva: Electronic resource; Zootaxa; Vol 4319, № 2 - Ustyuzhanin P. Ya. Petr Yakovlevich; Rekelj Ju. Juri; Kovtunovich V. N. Vasily Nikolaevich; Ustyuzhanina A. K. Anna Konstantinovna (2017, 2017)
Title screen